The Effect of Internal Control System Towards Sustainable Quality Governance in A State University: Basis for Establishing a Sustainable Quality Governance in State University - Borbe, Candy Angelica B. (Future Science / FSH-PH Publications, 2024)
This study aimed to determine the relationship between the internal control system and quality governance in a State University, Laguna State Polytechnic University (LSPU). The 110 Administrative Council of LSPU were the respondents, and the survey questionnaire was used to measure the level of implementation of Internal Control System components such as Control environment, Risk Assessment, Control Activities, Information and Communication and Monitoring and the observance of elements of governance such as Transparency, Accountability, Participation and Predictability in LSPU. The findings showed a significant relationship between Internal Control System and quality Governance. Monitoring, Information and Communication components significantly impacted the sustainability of quality governance. The researcher recommended a more comprehensive assessment of the internal control system, with a focus on monitoring and information and communication, which negatively affect governance quality. The study also suggested using interviews or direct observation for data collection.